ExpenseEase - living expenses management mobile application / Nurul Amira Muhamad and Faiqah Hafidzah Halim - Muhamad, Nurul Amira; Halim, Faiqah Hafidzah (Faculty of Computer and Mathematical Sciences, 2023)
Managing personal expenses is crucial, especially for students who often face financial difficulties. A recent survey reveals that many university students struggle with expense management due to a lack of knowledge. Although several expense management apps are available, most of them fail to meet the specific needs of students, particularly when it comes to quickly recording expenses. To address this gap, this project aims to develop a mobile application called ExpenseEase, a user-friendly and feature-rich mobile app designed to help students and young adults effectively manage their finances. Whether you are a college student or a young professional, this app is tailored to suit your unique needs and challenges when it comes to handling expenses. The project adopts a waterfall methodology, encompassing three phases: requirement, design, and implementation. In the requirement phase, a survey was conducted to gather requirements and analyze them. Subsequently, during the design phase, the interface, system, and database were designed. Finally, in the implementation phase, a functional system was developed, empowering users to effectively manage their expenses. This application utilized the capability of Optical Character Recognition (OCR) to scan receipts faster. Looking ahead, there are two potential areas for future work. First, integrating the application with financial institutions would allow students to securely link their bank accounts, providing real-time transaction updates, balance tracking, and automatic expense categorization. Second, incorporating reminders or notifications would assist users in staying on track with their financial goals and prompt them to log their expenses regularly.